Photosynthesis, Soluble and Structural Carbon Compounds in Two Mediterranean Oak Species (Quercus pubescens and Q. ilex) after Lifetime Growth at Naturally Elevated CO2 Concentrations - Blaschke, L.; Schulte, M.; Raschi, A.; Slee, N.; Rennenberg, H.; Polle, A. (Plant Biology, 2001)
Abstract: To study physiological responses of mature forest trees to elevated CO2 after lifetime growth under elevated atmospheric CO2 concentrations (pCO2), photosynthesis, Rubisco content, foliar concentrations of soluble sugars and starch, sugar concentrations in transport tissues (phloem and xylem), structural biomass, and lignin in leaves and branches were investigated in 30- to 50-year-old Quercus pubescens and Q. ilex trees grown at two naturally elevated CO2 springs in Italy. Ribulose-1,5-bisphosphate carboxylase/oxygenase content was decreased in Q. pubescens grown under elevated CO2 concentrations, but not in Q. ilex. Photosynthesis was consistently higher in Q. pubescens grown at elevated CO2 as compared with “control” sites, whereas the response in Q. ilex was less pronounced. Stomatal conductance was lower in both species leading to decreased transpiration and increased instantaneous water use efficiency in Q. pubescens. Overall mean sugar + starch concentrations of the leaves were not affected by elevated pCO2, but phloem exudates contained higher concentrations of soluble sugars. This finding suggests increased transport to sinks. Qualitative changes in major carbon-bearing compounds, such as structural biomass and lignins, were only found in bark but not in other tissues. These results support the concept that the maintenance of increased rates of photosynthesis after long-term acclimation to elevated pCO2 provides a means of optimization of water relations under arid climatic conditions but does not cause an increase in aboveground carbon sequestration per unit of tissue in Mediterranean oak species.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Carbohydrate; climate change; Elevated CO2; Lignin; photosynthesis; Rubisco